2007
DOI: 10.1002/14651858.mr000001.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Handsearching versus electronic searching to identify reports of randomized trials

Abstract: Handsearching still has a valuable role to play in identifying reports of randomized trials for inclusion in systematic reviews of health care interventions, particularly in identifying trials reported as abstracts, letters and those published in languages other than English, together with all reports published in journals not indexed in electronic databases. However, where time and resources are limited, searching an electronic database using a complex search (or the Cochrane HSSS) will identify the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 49 publications
2
164
1
1
Order By: Relevance
“…Articles were limited to the English language and human subjects. A hand search of the reference list from reviews and selected articles was also conducted to ensure a complete search (Hopewell et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Articles were limited to the English language and human subjects. A hand search of the reference list from reviews and selected articles was also conducted to ensure a complete search (Hopewell et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…A systematic review that compared hand-searching (as gold-standard) with the results of searching electronic databases to identify reports of randomized controlled trials (RCTs), showed that only 55 % of the RCTs were retrieved in MED-LINE and 49 % in Embase [24].…”
Section: Choice Of the Source Databases And Search Enginesmentioning
confidence: 99%
“…The changes to the search were balanced by the contact with experts, and for this reason the other articles excluded by the line of free-text were not reviewed. The three papers confirm that contact with experts (McManus et al, 1998) and hand searching (Hopewell, Clarke, Lefebvre, & Scherer, 2007) can be useful supplements to database searches.…”
Section: Resultsmentioning
confidence: 53%